NEUTRALITY AS A JUDICIAL VIRTUE: ESSENCE, SIGNIFICANCE AND RELATED TERMS - Hadži Stević, Brano (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2025)
Usually, the key characteristic of courts and judges is their independence. More precisely, the independence of a court concerns its separation from other branches (functions) of state power that do not have command or supervisory powers over courts, while the independence of a judge concerns the absence of influence on him by other (especially state) entities regarding the conduct and outcome of the process. In addition, it is important that judges decide impartially, i.e., that they act without prejudice towards the participants in the judicial process. In other words, a judge must treat the participants in the process (e.g., the prosecutor and the defendant) equally, i.e., he must not be biased towards any of them.Without diminishing the importance of the independence and impartiality of judges, we believe that it is equally valuable to analyze the neutrality of a judge, i.e., the judge's attitude towards the positive law. When a judge reasons legally, he is obliged to consider the applicable law as the exclusive reason for deciding and justifying the decision, i.e., the role of a judge is not to evaluate the substantive validity of the positive law, but to apply it. In other words, it is not up to the judge to correct the substantive errors of the legislator or other lawmaker.If a judge evaluates the applicable law and deviates from it due to his own substantive (e.g., moral) views, then one cannot speak of legal reasoning. This does not mean that the judge should ignore the values ​​contained in the positive law, but rather that the judge must not replace the lawmaker's value judgments implemented in law with his own value judgments, since the judge's duty is to resolve disputes from the legal point of view.
Keywords: judge; independence; impartiality; neutrality; positive law; values